IMPLEMENTATION OF SIX SIGMA AND KAIZEN TO IMPROVE THE QUALITY OF HEALTH PLASTER PRODUCTS IN THE COATING PROCESS - Janah, Ragillia Fitri Nur; Wahyuni, Hana Catur (Journal for Technology and Science, 2024)
General Background: Product quality control is essential to ensure consistent quality from the beginning to the end of the production process. Specific Background: PT. FGH faces significant quality challenges, specifically during the health plaster coating stage, which has resulted in numerous product defects. Knowledge Gap: Although previous research has applied Six Sigma for quality improvement, detailed studies on health plaster manufacturing using combined Six Sigma and 5S Kaizen methodologies remain limited. Aims: This study aims to assess the product defect rate at PT. FGH using the Six Sigma methodology, measure defect levels via the sigma level through Defect Per Million Opportunities (DPMO) conversion, and propose improvement strategies through 5S Kaizen. Results: Findings reveal a DPMO of 7,039.4959, with a sigma level of 3.96, indicating that while the process capability values for Cp and Cpk are 1.00, suggesting production aligns with specification limits, tighter monitoring is required. Notably, product defects are predominantly folding, perforated edges, and asymmetry, comprising 80% of defects and leading to financial losses of IDR 340,524,744 over a one-year period. Novelty: This study uniquely combines Six Sigma and 5S Kaizen in addressing specific defect types and sources, including mechanical and human factors, within the health plaster industry. Implications: By implementing targeted process improvements, this research contributes a practical framework for defect reduction and cost mitigation in production, supporting broader quality control efforts in similar manufacturing sectors.